Analisis Manajemen Sarana dan Prasarana dalam Meningkatkan Kualitas Pembelajaran di SDN 03 Tunggak - Valentina Febrianti; Ferina Agustini; Mei Fita Asri Untari (STKIP Andi Matappa Pangkep, 2022)
The problem in this research is the quality of learning at SDN 03 Tunggak is still very low. This can be seen from the principal's, teachers' and administration's rooms into one room, the school library which is no longer in use, there is no science laboratory room, there is no UKS room, and there is no warehouse. This study aims to determine and describe the condition of facilities and infrastructure, quality of learning, management of facilities and infrastructure, supporting and inhibiting factors of facilities and infrastructure management. This type of research is qualitative research using data collection procedures of observation, interviews, documentation, listening and notes. The results of this study indicate that the condition of the infrastructure is quite complete and the condition is quite good. The quality of learning has been maximized. Management of facilities and infrastructure has been running according to the regulations that have been set. Supporting factors for infrastructure management include community cooperation in maintaining infrastructure facilities, obtaining BOS funds and grants. The inhibiting factor is the lack of funds and student management in borrowing infrastructure.